2017
DOI: 10.1177/0095244317734394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unsaturation on physicochemical properties of maleic anhydride–grafted acrylonitrile butadiene styrene terpolymer

Abstract: In order to find out the shift of ductile nature of acrylonitrile-butadiene-styrene (ABS) polymer to brittle nature while maleic anhydride (MA) grafting, the iodine value of different MA-grafted ABS (MA-g-ABS) sampled has been determined. The iodine value of thermoplastic polymer is found by Wijs method with slight modification to overcome the poor solubility of thermoplastics in tetrachloromethane. Different samples with varying MA content were prepared using internal mixer. All the specimens were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Report [ 21 ] assumes the thermal stability reduction may be due to two factors: residual amounts of unreacted MA in ABS matrix; or molecular weight decrease. ABS‐MA (2.5% MA/0.5% DCP) showed the lowest thermal stability probably due to the higher molecular weight reduction as corroborated through torque rheometry and MFR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Report [ 21 ] assumes the thermal stability reduction may be due to two factors: residual amounts of unreacted MA in ABS matrix; or molecular weight decrease. ABS‐MA (2.5% MA/0.5% DCP) showed the lowest thermal stability probably due to the higher molecular weight reduction as corroborated through torque rheometry and MFR.…”
Section: Resultsmentioning
confidence: 99%
“…Manaf et al [ 21 ] investigated ABS functionalization with MA, using DCP as initiator. FTIR spectra indicated the MA grafts in ABS, producing 1780 cm −1 band.…”
Section: Introductionmentioning
confidence: 99%
“…The grafting of MA slightly reduces the thermal stability of pristine ABS and showed T onset and T d at 308°C and 372°C, respectively. The reduction is because of the decrease in the molecular weight of MA‐ g ‐ABS during the MA grafting process or because of the presence of trace quantity of unreacted MA in the polymer matrix . It indicates that MA grafting slightly lowers its thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…used the MA‐ g ‐ABS as a compatibilizer for ABS/polycarbonate (PC) alloy and it was also observed that there was 70% reduction in impact strength while GD increased from 0 to 2.5 wt% . Recently, we could quantify the percentage reduction of unsaturation in different MA‐ g ‐ABS samples in terms of iodine value . The limitations associated with grafting of MA on ABS have encouraged for modifying MA‐ g ‐ABS via simple mixing of an external modifying agent.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to observe for PLAr a single decomposition step initiated within the range of 250 to 352 °C, indicating that it presented less thermal stability, when compared to PLA. As the PLAr showed lower molar mass and degree of crystallinity, thermal stability decreased (Manaf et al, 2018;Becena, 2005). The PLA/PLAr blend (25%) hardly changed the thermal decomposition behavior, when compared to neat PLA.…”
Section: Thermogravimetry (Tg)mentioning
confidence: 99%